2019
DOI: 10.1080/16742834.2019.1641397
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced correlation between ENSO and western North Pacific monsoon during boreal summer around the 1990s

Abstract: The correlation between summertime Niño3.4 index and western North Pacific (WNP) summer monsoon index has strikingly enhanced since the early 1990s, with nonsignificant correlation before the early 1990s but significant correlation afterward. This observed interdecadal change around the 1990s may be associated with more frequent occurrences of central Pacific (CP) El Niño and the interdecadal changes in ENSO-associated SST anomalies. During the post-1990s period (the pre-1990s period), highly noticeable tropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…It has been reported that cooler (warmer) SST in the tropical central and eastern Pacific can favor less (more) rainfall over the tropical WNP and thus an anticyclonic (cyclonic) anomaly to the northwest (Lau and Nath 2006;Wang et al 2013). These results are also consistent with some recent studies (He and Wu 2018;Wu and Wang 2019), who reported that the tropical WNP precipitation or anticyclonic anomaly is more associated with the simultaneous SST anomalies in the tropical central and eastern Pacific in the recent decade.…”
Section: Possible Mechanismsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been reported that cooler (warmer) SST in the tropical central and eastern Pacific can favor less (more) rainfall over the tropical WNP and thus an anticyclonic (cyclonic) anomaly to the northwest (Lau and Nath 2006;Wang et al 2013). These results are also consistent with some recent studies (He and Wu 2018;Wu and Wang 2019), who reported that the tropical WNP precipitation or anticyclonic anomaly is more associated with the simultaneous SST anomalies in the tropical central and eastern Pacific in the recent decade.…”
Section: Possible Mechanismsupporting
confidence: 91%
“…Xu et al (2019) also suggested that the convection location and easterly shear over the tropical WNP result in the weakened and eastward shifted teleconnection after the late 1990s. Furthermore, some studies discussed the role of ENSO evolution in affecting the components of the teleconnection (Yim et al 2008b;He and Wu 2018;Huang et al 2018;Wu and Wang 2019;Huang et al 2020), but these studies mainly focused on the tropical anomalies rather than the tropical-extratropical couplings. In this study, we would show a comprehensive breakdown of the meridional teleconnection in the early 2000s, focusing on the tropical-extratropical connections, and explore the possible role of tropical SSTs in inducing the breakdown of teleconnection.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, stronger coupling between the JJA Niño3.4 SST and JJA tropical Indian Ocean SST anomalies could be identified during this period (Wang and Yu 2018). The warm JJA western North tropical Indian Ocean SST anomalies could hamper and cancel out the influences of JJA warm Niño3.4 SST anomalies on the WNPSM, resulting in the weakening of the WNPSM-ENSO correlation (Wu and Wang 2019). In contrast, stronger ENSO-Indian Ocean coupling may support an active ISM (e.g., Wang and Yu 2018;Srivastava, Chakraborty, and Nanjundiah 2019), possibly with stronger variations and closer associations with ENSO.…”
Section: Resultsmentioning
confidence: 87%
“…However, the correlation analysis between the Niño3 index and TCGF in the WNP during July and August showed a correlation of −0.16, which is statistically insignificant. However, previous studies (Cao et al ., 2018; Liu and Chen, 2018; Zhao and Wang, 2018; Wu and Wang, 2019; Zhao et al ., 2019) have suggested that there are significant decadal changes in the correlation between WNP TCGF/monsoon and ENSO around 1990s (not significant before 1990s, but become significant after 1990s). Thus, a partial correlation analysis was conducted to examine whether the ENSO influenced the high positive correlation between HWD in Korea and TCGF in the WNP during July and August (Table 2).…”
Section: Resultsmentioning
confidence: 99%